2019
DOI: 10.1016/j.plabm.2019.e00135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diabetes Care parameters in capillary blood collected with a novel sampling device

Abstract: ObjectivesThe aim of this study was to determine whether the Hem-Col method of obtaining and storing blood is an acceptable alternative to venepuncture for measuring Diabetes Care parameters. Design and methods: Hem-Col is a novel blood collection device that is designed to collect capillary blood drawn with a finger prick. Hem-Col is a microtube containing an anticoagulant and a preservation buffer to enhance analyte stability in whole blood. The Diabetes Care parameters cholesterol, creatinine, HbA1c, high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…When patients had no symptoms but requested a test, the date of onset of symptoms was not registered. Sera were self-collected by finger prick as described earlier using Hem-Col which is a novel blood collection device that is designed to collect capillary blood drawn with a finger prick [ 10 ]. Hem-Col is a microtube containing an anticoagulant and a preservation buffer to enhance analyte stability in whole blood.…”
Section: Methodsmentioning
confidence: 99%
“…When patients had no symptoms but requested a test, the date of onset of symptoms was not registered. Sera were self-collected by finger prick as described earlier using Hem-Col which is a novel blood collection device that is designed to collect capillary blood drawn with a finger prick [ 10 ]. Hem-Col is a microtube containing an anticoagulant and a preservation buffer to enhance analyte stability in whole blood.…”
Section: Methodsmentioning
confidence: 99%
“…Self-management is becoming increasingly important in healthcare [ 18 ]. It can reduce unscheduled care by improving disease control and quality of life, potentially reducing costs, and improving healthcare outcomes as a result [ 19 ]. At-home blood-sampling empowers patients by allowing them to take more control of their own healthcare [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients have control over where and when they want to perform the blood sampling, which reduces the possible disruption of their daily routines. Importantly, blood does not have to be sampled via venipuncture but can be collected with a finger prick, which is less invasive [ 19 ]. It has been shown that patients prefer a finger prick over venipuncture [ 21 , 22 ], mainly since it is experienced as being less painful, although contradictory results have also been reported [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations